2007
DOI: 10.1002/biof.5520310103
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry leaves protect rat tissues from immobilization stress‐induced inflammation

Abstract: The ability of the antioxidants in the mulberry leaves to protect Sprague-Dawley rats from injuries caused by immobilization stress was studied as an indicator of the tissue bioavailability of antioxidants. Nitrite level, lipid peroxidation and total antioxidant activity (TAA) in the plasma and tissues were measured. There were hypertrophy of the adrenal glands and kidneys, significant increased levels of nitrite in the plasma and adrenal glands, elevated thiobarbituric acid reactive substances (TBARS) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
5
18
0
Order By: Relevance
“…This finding is in agreement with earlier reports that acute stress activates iNOS and enhances anxiety in rodents [10,11]. Acute immobilization stress, as used in the present study, is reported to increase expression of iNOS in brain cortex and leads to production of the stable nitric oxide metabolites (nitrite and nitrate) in both plasma and brain [5,8].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This finding is in agreement with earlier reports that acute stress activates iNOS and enhances anxiety in rodents [10,11]. Acute immobilization stress, as used in the present study, is reported to increase expression of iNOS in brain cortex and leads to production of the stable nitric oxide metabolites (nitrite and nitrate) in both plasma and brain [5,8].…”
Section: Discussionsupporting
confidence: 95%
“…In brain, NOS has been localized in regions involved with anxiety, such as hypothalamus, amygdala and hippocampus [7]. Immobilization stress in rats has been reported to significantly increase plasma nitrite levels [8]. A differential role is played by neuronal and inducible isoforms of NOS in anxiety in mice under unstressed and stressed conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Acute immobilization stress, as used in the present study, is reported to increase expression of iNOS in the brain cortex and leads to production of the stable nitric oxide metabolites (nitrite and nitrate) in both plasma and brain (4,33). The stressor used in the present study (6-h immobilization) has been found to increase TNF-α levels (4).…”
Section: Discussionmentioning
confidence: 52%
“…A differential role is played by neuronal and in-ducible isoforms of NOS in depression in mice under unstressed and stressed conditions. Acute restraint stress has been observed to significantly increase expression of iNOS and plasma nitrite levels in rodents [8][9][10] . Aminoguanidine, an inhibitor of inducible NOS, reversed stress-induced depression-like behavior in rats.…”
mentioning
confidence: 99%